PENERAPAN MODEL HANNAFIN DAN PECK UNTUK MENGUJI PENERIMAAN DAN KEPUASAN SISWA TERHADAP PEMBELAJARAN PAI - Hamdani Bakhtiar, Yusup (Asaatidzah, 2023)
Everything is digital in this era of Industrial Revolution 4.0. Children are used to using electronic devices. Therefore, parents and educators need to work extra hard so that children can use electronic devices as learning tools. Teachers need to be clever and imaginative in choosing learning models or approaches that will be used with students in Islamic Religious Education classes. It is important for educators to be imaginative and creative when creating new teaching strategies. The aim of this qualitative research methodology is to understand the phenomena encountered by research subjects. The needs analysis phase, design phase, and development and implementation phase form Hannafin and Peck's three stages of the instructional design paradigm. Benefits: Because this model is product-oriented, it can produce learning products. Each element of this model involves assessment and repetition. Finding gaps at an early stage can help in the analytical stage. Meanwhile, the disadvantage of this paradigm is that it is only limited to specific problems and cannot be applied to generic problems because it is more inclined towards media creation.